Pattern of Drugs and Therapeutic Agents Exposure among Pediatric Inpatients in the Fatima University Medical Center - Subedi, N; Shrestha, B; Poudel, S; Bhattarai, A; KC, Namrata (Journal of Gandaki Medical College-Nepal, 2018)
Background: Drugs and therapeutic agents exposure is essentially universal for persons, young and old in the Philippines. In the hospital, many drugs and therapeutic agents are being given to the patients according to severity of the illness. The evidence has suggested that complex medication combination increase the risk for adverse drug events. The most common results of many drugs and therapeutic agents are increased adverse drug reactions, drug-drug interactions and higher costs.Objectives: To assess the prevalence and patterns of exposure to drugs and therapeutic agents among pediatric inpatients.Methods: Study Design: Retrospective study. Setting: Pediatric inpatients in the Fatima University Medical Center. Patients: A total of 1075 patients younger than 19 years, excluding healthy newborn, hospitalized in 2011, representing a part of pediatric inpatients in the Philippines.Results: The most common exposure was with D5.3NaCl, paracetamol, cefuroxime, salbutamol, zinc sulphate. Most of the pediatric inpatients received five or less number of medication varied by age and length of stay in the hospital. Pediatric inpatients were exposed to numerous drugs and therapeutic agents, especially patients with dengue III.Conclusions: A large portion of pediatric inpatients are exposed to numerous drugs and therapeutic agents, especially patients with Dengue III. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 23-28